Tumour GDF-15 Expression and Clinical Outcomes in Intermediate-Risk Metastatic Clear-Cell Renal Cell Carcinoma Treated with Second-Line Nivolumab - Orhun Akdogan; Betul Ogut; Osman Sutcuoglu; Melike Urganci; Burcu Ulas Kahya; Ipek Isik Gonul; Hatice Azra Begum Salimoglu; Tuba Ugur Tuzcu; Ozan Yazici; Ahmet Ozet; Nuriye Ozdemir (Current Oncology, 2026)
Background: Immune checkpoint inhibitors have improved outcomes in metastatic clear-cell renal cell carcinoma (mRCC), yet clinically applicable tissue biomarkers remain limited. Growth differentiation factor-15 (GDF-15) promotes tumour immune evasion and has emerged as a potential therapeutic target in immuno-oncology. We evaluated the prognostic significance of tumour GDF-15 expression in patients with intermediate-risk clear-cell mRCC treated with second-line nivolumab. Methods: Forty-six patients with intermediate-risk clear-cell mRCC who received nivolumab after one line of tyrosine kinase inhibitor therapy were retrospectively evaluated. Tumour GDF-15 expression was assessed by immunohistochemistry and classified as low (0–1+) or high (2–3+). Objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and the development of cancer-associated cachexia were compared between expression groups. Results: High tumour GDF-15 expression was observed in 23 patients (50%). ORR was significantly higher in the low-expression group than in the high-expression group (57% vs. 26%, p = 0.036). Low tumour GDF-15 expression was associated with significantly longer PFS (24.5 vs. 7.5 months; HR 0.38, 95% CI 0.18–0.80; p = 0.009) and OS (28.6 vs. 12.6 months; HR 0.43, 95% CI 0.19–0.98; p = 0.041). The association with OS remained significant after adjustment for age. The frequency of cancer-associated cachexia did not differ according to tumour GDF-15 expression (43% vs. 35%, p = 0.546). Conclusions: Low tumour GDF-15 expression was associated with better objective response and longer progression-free and overall survival in patients with intermediate-risk metastatic clear-cell renal cell carcinoma treated with second-line nivolumab, with the association with overall survival remaining significant after adjustment for age. Tumour GDF-15 represents a promising tissue biomarker for prognostic risk stratification and warrants validation in larger prospective studies.